Pengaruh Lingkungan Pondok Pesantren dan Pembelajaran Talimul Mutaalim Terhadap Prestasi Belajar Siswa Di SMP Askhabul Kahfi Semarang - Andika Akhmad Maulana; Raharjo Raharjo (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to determine the influence of the Islamic boarding school environment and the Talimul Mutaalim learning process on student learning achievement at Askhabul Middle School, Semarang. This research uses a quantitative type of research. The research sample consisted of 60 students at Askhabul Middle School, Semarang, using simple random sampling techniques. Data analysis uses correlation and multiple regression techniques. The results of this research are that the influence of the Islamic boarding school environment (X1) on student learning achievement (Y) is 0.087 < 0.05 and the Tcount value is 1.740 > Ttable 2.002. The influence of the Talimul Mutaalim learning process (X2) on student learning achievement (Y) is 0.001 < 0.05 and the T value is 8.753 > T table 2.002. The influence of the Islamic boarding school environment (X1) and the Talimul Mutaalim learning process (X2) simultaneously on student competency (Y) is 0.001 < 0.05 and the Fcount value is 59.198 > Ftable 3.16. These results show that there is a positive influence between the Islamic boarding school environment on student learning achievement, the influence of Talimul Mutaalim learning on student learning achievement and there is a simultaneous influence of the Islamic boarding school environment and the Talimul Mutaalim learning process on student learning achievement.